2019
DOI: 10.1016/j.molliq.2019.111986
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of thermo-optical properties of SiO2/Ag–CuO nanofluid for direct absorption solar collectors

Abstract: Augmenting thermal and optical properties of working fluids used in solar thermal conversion systems using hybrid nanomaterials is gaining prominence. In the present study photo-thermal analysis and thermal conductivity investigations were performed on SiO2/Ag-CuO binary water based nanofluid. The influence of particle concentration and surfactant concentration on thermo-optical properties were investigated using the design of experiment concept. Analysis of variance (ANOVA) was employed to study the significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…[35] It has been proved by some effective principles that metal oxide nanocomposites have excellent light absorption ability. [36] In the present study, Joseph et al [37] investigated photothermal and thermal conductivity research of SiO 2 /Ag-CuO nanofluid. Jin et al [38] studied the Fe 3 O 4 , Cu and Au hybrid nanofluids which characterized to heighten the optical property in DASCs.…”
Section: Introductionmentioning
confidence: 89%
“…[35] It has been proved by some effective principles that metal oxide nanocomposites have excellent light absorption ability. [36] In the present study, Joseph et al [37] investigated photothermal and thermal conductivity research of SiO 2 /Ag-CuO nanofluid. Jin et al [38] studied the Fe 3 O 4 , Cu and Au hybrid nanofluids which characterized to heighten the optical property in DASCs.…”
Section: Introductionmentioning
confidence: 89%
“…[69] 2015 Al2O3-H2O The collector productivity was increased more than pure water for all four concentrations of the nanofluid. [70] 2019 SiO2 / Ag-CuO The stability of nanofluids vigorously influenced the optical and thermal properties of the nanofluid.…”
Section: Materials and Methods Utilization Of Nanofluids In Solar Collementioning
confidence: 99%
“…The hybrid boron nitride (BN) and carbon black (CB) nanofluids were investigated by Hazra et al 28 They reported that BN-CB nanofluids at the concentration of 90 ppm/15 ppm enhanced the collector efficiency by 34.55%. Some other hybrid nanofluids such as ZnO-Au, 40 Al 2 O 3 /Co 3 O 4, 41 SiO 2 /Ag-CuO, 42 and Ag-Al 2 O 3 43 have also been proposed for DASC applications. The literature review above indicates that noble metals show the LSPR effect, and the hybrid nanofluids containing noble metals present excellent light absorption ability.…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid boron nitride (BN) and carbon black (CB) nanofluids were investigated by Hazra et al 28 They reported that BN‐CB nanofluids at the concentration of 90 ppm/15 ppm enhanced the collector efficiency by 34.55%. Some other hybrid nanofluids such as ZnO‐Au, 40 Al 2 O 3 /Co 3 O 4, 41 SiO 2 /Ag‐CuO, 42 and Ag‐Al 2 O 3 43 have also been proposed for DASC applications.…”
Section: Introductionmentioning
confidence: 99%